Liver cirrhosis in cystic fibrosis--therapeutic implications and long term follow up. Issue 5 (May 1993) - Feigelson, J; Anagnostopoulos, C; Poquet, M; Pecau, Y; Munck, A; Navarro, J
Abstract : Experience gained from liver studies in 450 patients with cystic fibrosis, seen in a 38 year period from 1964 to 1992, is surveyed. Of these, 31 (7%) showed findings that indicated multilobular cirrhosis. There was a slight but not significant male predominance: 19 males against 12 females. Liver disease had its onset during childhood in most cases. The natural course of liver disease and of cirrhosis is protracted. All patients were routinely evaluated by way of: (i) clinical examination, (ii) biochemical studies and specifically estimation of transaminases and gamma glutamyltransferase, and (iii) liver imaging, ultrasonography, and computed tomography. The study aimed to detect early liver disease, that is multilobular cirrhosis and its complications, with a view to optimal introduction of treatment with ursodeoxycholic acid as this drug shows promise for preventing or stabilising the cirrhotic process. Effects of surgical treatment on portal hypertension are surveyed. These include portacaval shunting, partial splenectomy (considered the procedure of choice), liver transplant in the event of liver failure, or a triple transplant (liver, lungs, and heart) if necessary. One triple transplant was successfully performed in a boy of 10 years with a 2 year follow up.